Distribusi Simulium Spp. (Diptera: Simuliidae) Pradewasa pada Kualitas Air dan Karakteristik Fisik Sungai Berbeda di Kabupaten Bogor - Nur Rustam, Sri Nur Rahmi; Hadi, Upik Kesumawati; Soviana, Susi (Jurnal Veteriner; Vol 20 No 4 (2019)DO - 10.19087/jveteriner.2019.20.4.511, 2019)
Simulium (black flies) are vector of Onchocerciasis in humans and animals. Preimaginal Simulium has most typical breeding habitat in clear water with fast-running water. This study aims to analyze the relationship between distribution of preimaginal Simulium with the water quality and the rivers physical characteristics. The study was conducted on October 2018 until January 2019 in three locations namely Cilember 1 and Cilember 2 (forest areas), and Pamijahan (rural area), Bogor Regency, West Java. Preimaginal Simulium collections, water quality, and rivers physical characteristics measurements were carried twice a month during four months. Identification was carried out under a microscope, and the data was analyzed by canonical correspondence analysis (CCA). The results showed that the distribution of preimaginal Simulium species in the forest areas (Cilember 1 and 2) were more diverse than in the rural area (Pamijahan). Seven species of black flies were found in Cilember 1, four species in Cilember 2, and two species in Pamijahan. The most abundance of black fly species found in Cilember 1 was S. (S.) eximium (43.25%), in Cilember 2 was S. (N.) feuerborni (88.71%), and in Pamijahan was S. (S.) nobile (99.12%). Based on CCA preimaginal Simulium species with high diversity were found in the rivers that have high dissolved oxygen (9.35±0.32 mg/L), low temperature (19.94±0.24ºC), low total dissolved solid (17.45±1.90 ppm), low conductivity (25.48±2.34 ?s), and low concentration of Coliform (0.43×103±0.25 cfu/ mL), and the physical characteristics of the rivers were wide (3.68 m), fast running-water (1.00±0.09 m/s), depth more than 0.1 m, and boulder streambed particles.